Design and Prototype of an Indoor Air Quality Monitoring System: A Case Study of Maternity Ward at Kabale Regional Referral Hospital. - Muhwezi, Methodius (Kabale University, 2024)
This project develops a Smart Indoor Air Quality Monitoring System for the maternity ward at KRRH, aimed at ensuring a safe environment for mothers and newborns. The purpose is to create an automated system that monitors air quality and temperature, ensuring optimal conditions in the maternity ward. The system uses an Arduino Uno with a DHT11 temperature and humidity sensor and an MQ135 air quality sensor. Data is displayed on a 16x2 LCD with I2C, and alerts are sent via a GSM module when thresholds are exceeded. A DC motor functions as an extractor fan for temperature and air quality control, and a red LED has very low humidity in the circulating air. The system successfully monitors and displays real-time temperature and air quality data. It sends alerts and activates responses (fan and LED) when predefined thresholds are surpassed. The prototype effectively integrates sensor data with real-time monitoring and alert capabilities, ensuring a safe maternity environment. Future improvements should focus on sensor calibration and system responsiveness to enhance reliability and functionality.